Identification of A Major Quantitative Trait Locus for Grain Weight In Rice Using Microsatellite Marker - Susilowati, Mariana; Aswidinnoor, Hajrial; Enggarini, Wening; Trijatmiko, Kurniawan Rudi (Makara Journal of Science, 2017)
Rice is one of the major staple foods in the world, especially in Asia. Improving yield potential of superior cultivars is important to meeting the demand for rice production, which is increasing due to human population increase, climate change, and degradation of agricultural resources, such as land and water. In this study, a BC3F2 population developed from an intraspecific cross between Ciherang and a new plant type line (B11143D) was used in a quantitative trait locus (QTL) analysis. Ciherang is a high yielding rice cultivar with good grain quality which has been planted in 37% of the irrigated rice area in Indonesia. The objective of this study was to identify QTL(s) for yield components on chromosome 12, which can be used to improve the elite cultivar Ciherang or other popular cultivars through marker-assisted breeding. A total of two hundred BC3F2 lines were evaluated in the greenhouse during this study. The population was observed for eight agronomic traits including days to heading (dth), plant height (ph), flag leaf length (fll), panicles per plant (ppl), panicle length (pl), grains per panicle (gpp), 1000-grain weight (gw), and yield (yld). Four simple sequence repeats (SSR) markers (RM3472, RM28048, RM28195, and RM1986) were used for targeted mapping on chromosome 12. Linkage analysis identified a QTL for 1000-grain weight located on chromosome 12 at position 53.5 cM–73 cM.